MEMBERDAYAKAN PERTANIAN BERKELANJUTAN MELALUI PRODUKSI PUPUK CAIR BERBASIS SUMBER DAYA LOKAL: DESA CIINJUK, KECAMATAN CADASARI, PANDEGLANG - Ipah Ema Jumiati; Shabrina Farhanadya; Indar Kustiningsih (SEBA: Jurnal Pengabdian kepada Masyarakat, 2025)
Ciinjuk Village, situated in the Cadasari Sub-District, Pandeglang City, is primarily an agricultural community. Its main livelihood revolves around farming. The village seeks alternative fertilizers for long-term sustainability without adverse effects. The development of liquid fertilizer based on local resources has become a focal point in sustainable agriculture. This study explores an innovative approach to crafting environmentally friendly liquid fertilizer through a collaboration between the residents of Ciinjuk Village and members of the Kumpulan Wanita Tani (KWT). The research encompasses the utilization of coconut water, EM4, palm sugar, and small bottles as raw materials. Through a fermentation process, these local ingredients are transformed into nutrient-rich liquid fertilizer teeming with beneficial microorganisms. The outcomes of this case study illustrate the active engagement of the community in fostering sustainable agricultural enhancement. Keywords: Liquid Fertilize; Local Resources; Fermentation, Microorganisms